Skrining Fitokimia serta Uji Aktivitas Antioksidan Ekstrak Etanol 96% Daun Kelor (Moringa Oleifera, Lam) dengan Metode DPPH (2,2-Difenil-1-Pikrilhidrazil) - Ni Luh Putu Junita Kusuma Dewi; Ni Made sukma Sanjiwani; I Gusti Agung Ayu Kusuma Wardani; I Wayan Surya Rahadi; I Wayan Sudiarsa; Ni Putu Ayu Mirah Mariati (Chemistry Department, 2025)
All parts of the moringa plant, from the roots, seeds, stems to the leaves, are known to have medicinal properties. Its reported uses include anti-inflammatory, antioxidant, antibacterial, antifungal, and diuretic properties. This study focused on examining the presence of secondary metabolites and assessing the antioxidant potential of 96% ethanol extracts of moringa leaves (Moringa oleifera, Lam). The type of research conducted was a laboratory experiment. Moringa leaves were extracted using the Ultrasound-Assisted Extraction (UAE) method with 96% ethanol as the solvent. The resulting extract was then evaporated using a rotary evaporator to obtain a concentrated extract of 34.8 grams. The secondary metabolite content was evaluated through phytochemical screening, and the antioxidant activity was tested using the DPPH (2,2-diphenyl-1-picrylhydrazil) method. The antioxidant strength was determined by calculating the IC₅₀ value, which indicates the percentage of free radical scavenging by the test sample, and by the AAI value, which describes the antioxidant activity index of the extract. Based on the phytochemical screening results, the 96% ethanol concentrated extract of moringa leaves contained secondary metabolite compounds such as saponins, alkaloids, tannins, and steroids. The IC₅₀ value obtained from the extract was 75.428 ppm with an AAI of 0.530. As a comparison, ascorbic acid showed an IC₅₀ of 14.295 ppm and an AAI of 2.798.